PENANAMAN NILAI TAUHID DALAM DAKWAH NABI MUHAMMAD SAW DI MEKKAH - Nuryanto Putra, Johanna; Nurzena (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The process of instilling the values of tawhid in the da’wah of the Prophet Muhammad (peace be upon him) during the Meccan period was shaped by the conditions of Jahiliyyah society, which was characterized by polytheism, moral crisis, and social inequality. This study aims to analyze the da’wah methods employed by the Prophet, the values of tawhid that were instilled, and their implications for social change within society. This study employs a qualitative approach using a literature review method, drawing from books, scientific journals, and relevant literature. The findings indicate that the Prophet’s da’wah in Mecca was conducted in stages through the sirriyah and jahriyah methods, utilizing persuasive, rational, and exemplary approaches. The values of tawhid were not only taught as theological concepts but also served as the foundation for shaping moral character and a just and civilized social order. Thus, tawhid played a central role as the primary foundation in the transformation of society from a state of ignorance (jahiliyah) toward a society of faith and morality